Photoinduced Quantum Tunneling Model Applied to an Organic Molecule - Drigo Filho, E. [UNESP]; Jubilato, K. H.P. [UNESP]; Ricotta, R. M. (Springer Nature, 2020)
The paper proposes a photoinduced quantum tunneling model of electron transfer through four quantum square wells potential to simulate the biological process of photosynthesis in bacteria. The problem is mathematically exact with mathematical transcendental equations solved graphically. This simplified model allowed the calculation of the characteristic tunneling times of the process. A comparison is made between the results obtained in the model and the experimental data of the organic molecule Rhodobacter sphaeroides photosynthetic process.
Keywords: Electron transfer; Photosynthesis; Potential wells; Quantum tunneling